PENERAPAN STRATEGI INDEX CARD MATCH (ICM) DISERTAI HANDOUT TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VIII SMPN 5 SOLOK SELATAN TAHUN PELAJARAN 2014/2015 - Yulita, Windra - (Pendidikan Biologi, 2014)
Background of this research is low studentâs result in learning biology at second grade of SMPN 5 Solok Selatan. One of effort which can do is applying Index Card Match (ICM) strategy with handout toward studentâs learning outcome at biology at second grade of SMPN 5 Solok Selatan in Academic Year of 2014/2015. Kinds of this research is experimental research design of the research is Randomized Control-Group Posttest Only Design. Population of the research is all of second grade students, semester 1 at SMPN 5 Solok Selatan of Academic Year of 2014/2015 which is three class. Sampling technique is purposive sampling. Hence, the class which chosen experiment is VIIIA and control class is VIIIB. The research instruments use multiple choice in final test. Analysis of the data is t test, with criteria th > tt. The result of biological from studies experiment class is 79,59, standard deviation 89,47 moreover, control class is 71,26, standard deviation 131,98. From analysis test got result th = 2,47 > tt = 1,68. Assessment studentâs of behavior and skill in experiment and control class were increase.